KARAKTERISTIK BUBUR BAYI INSTAN BERBAHAN DASAR TEPUNG BERAS MERAH DENGAN PENAMBAHAN EKSTRAK DAUN KELOR (MORINGA OLEIFERA LAM) - Nilmawati Husain; rosdiani Azis; Adnan Engelen (Program Studi Teknologi Hasil Pertanian, Politeknik Gorontalo, 2020)
cooking process is not required. At the age of 6 months, babies need complementary foods for ASI (MP-ASI). Generally, instant baby porridge circulating in Indonesia is made with the main ingredients of white rice and brown rice, which are known as the main staples. In this study the researchers wanted to experiment with adding brown rice and Moringa leaf extract. This study aims to determine the level of preference for instant baby porridge with a combination of red rice flour with the addition of Moringa leaf extract, to determine the content of some chemical properties in instant porridge. The method used in this thesis is a method of testing organoleptic tests, water content tests, ash content tests, viscosity, and absorbency tests. The data needed is then tested using the RAL method and continued with the LSD test if there is a real effect. The stages in this final project include conducting a literature study, data collection, and analysis. The testing technique used is organoleptic test, water content test, ash content test, viscosity test, and absorbency test. The results showed that the organoleptic test results had a preference level resulting from three treatments of instant baby porridge made from red rice flour and moringa leaf extract as a whole were on a scale of 5.61-6.92 or in the usual up to very high level. And instant baby porridge that is favored by panelists or the public is A1 treatment of instant baby porridge made from red rice flour with the addition of Moringa leaf extract. Whereas in the chemical properties test, the best treatment is A3 treatment with 300 gr red rice flour substitution with the addition of 90 ml Moringa leaf extract